New occurrences of Corallium spp. (Octocorallia, Coralliidae) in the Central Northeast Atlantic - Sampaio, Íris (2010)
Corallium niobe Bayer, 1964 and Corallium tricolor (Johnson, 1899) are reported as new records from the central Northeast Atlantic. C. niobe was caught in the Azores and C. tricolor on the slope of the Irving Seamount (South Azores Seamounts). The presence of Corallium johnsoni Gray, 1860 in Azorean waters is confirmed. The sub-tropical Macaronesian islands and seamounts appear to be an important hot-spot for Corallium spp. Most colonies have been collected on seamounts and island slopes around Madeira, Canaries, Azores and the Cape Verde archipelagos. In the Azores most of these corals live below the normal depth of commercial fishing operations and are unlikely to be severely impacted by this activity.